PEMECAHAN MASALAH MATEMATIKA SISWA SMP DITINJAU DARI KECERDASAN INTRAPERSONAL - Nur Rokhima; Harina Fitriyani (Universitas Muhammadiyah Semarang, 2017)
Problem solving is one of the 21st century skills which should be masteredby all of students. In a class, every students have different characteristicand intelligent. The aim of this research is to describe the profile of student’s mathematics problem solving based on intrapersonal intelligent. This research used descriptive qualitative approach. The subjects of this study were 3 students of grade 8 of SMP Muhammadiyah 1 Kalasan Yogyakarta which consist of student in high, middle, and low interpersonal intelligent. Technique of collecting data usedquestionnaire, problem solving test and interview. And analysis data usedMilles and Huberman model that is reduction, interpretation and conclusion. The result of this research shown that high intrapersonal intelligent student solved the mathematics problem by Polya’s stage perfectly. While the middle intrapersonal intelligent sudent only able to understand the problem, planning, carring out the plan without looking back the answer when solve mtahematics problem. As for the low intrapersonal intelligent student was less able to solve the problem inevery stage of Polya’s stage. Keywords: Problem solving, Intrapersonal Intelligence